How Large Is Wisconsin's Budget Gap for the 2011-13 Biennium? - Reschovsky, Andrew (My University, 2010)
With adjustments to the Legislative Fiscal Bureau's July 2010 determination of Wisconsin's fiscal condition at the beginning of the upcoming biennium, the author estimates as much as a $3 billion structural fiscal deficit for 2011-13. He adjusts the LFB number for to account for both increases in the costs of providing public services and the additional revenues that economic growth will generate.